2013
DOI: 10.2306/scienceasia1513-1874.2013.39.331
|View full text |Cite
|
Sign up to set email alerts
|

The genus Morinda (Rubiaceae) in Thailand

Abstract: The genus Morinda (Rubiaceae) is revised and presented with a key to species, descriptions with distributional and ecological data, together with illustrations of some species. Nine species are considered, one of which is divided into two varieties. Two species and one variety are endemic to the country. M. talmyi is typified. M. longifolia and M. pumila are reduced to synonymy with M. pandurifolia and M. tomentosa, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The leaves are petiolate or subsessile with a stalked head of flowers that fuse together at their ovaries. The fruits were produced in ellipsoidal shapes that fused together known as syncarp (Kesonbuaa and Chantaranothai, 2013). Taxonomic studies in Malaysia have identified the Morinda genus as comprising nine species in Peninsular Malaysia, including three species with reported phytochemistry (M. citrofolia, M. elliptica, and M. umbellate), and six recorded species (M. corneri, M. lacunose, M. rigida, M. calciphila, M. scortechinii, and M. ridleyi) (Wong, 1984;Abdullah et al, 1998).…”
Section: Genus Morindamentioning
confidence: 99%
“…The leaves are petiolate or subsessile with a stalked head of flowers that fuse together at their ovaries. The fruits were produced in ellipsoidal shapes that fused together known as syncarp (Kesonbuaa and Chantaranothai, 2013). Taxonomic studies in Malaysia have identified the Morinda genus as comprising nine species in Peninsular Malaysia, including three species with reported phytochemistry (M. citrofolia, M. elliptica, and M. umbellate), and six recorded species (M. corneri, M. lacunose, M. rigida, M. calciphila, M. scortechinii, and M. ridleyi) (Wong, 1984;Abdullah et al, 1998).…”
Section: Genus Morindamentioning
confidence: 99%
“…In preparation for the upcoming Rubiaceae volumes in the Flora of Thailand, nine species were recognized in a recent publication (Kesonbua & Chantaranothai, 2013), and updates to this publication are presented here. Morinda pandurifolia Kuntze is now placed in synonymy under M. persicifolia Buch.-Ham., in agreement with the World Checklist (Govaerts et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the new combination at species level is required. Pitard (1924) described Morinda persicifolia var. talmyi and cited M. talmyi Pierre mss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…are treated as synonyms to M. pubescens and accordingly this is followed in this work and the published work reported on these species is cited as related to M. pubescens. M. tomentosa which is now known as M. pubescens is widely distributed in India, Sri Lanka, China, central Myanmar, southern Thailand, Vietnam, and Indonesia (Kesonbuaa & Chantaranothai 2013). It is a small evergreen tree adapted to grow successfully in arid/semi-arid to mesophytic conditions (Bermer & Manen 2000).…”
mentioning
confidence: 99%